Improved anti-viral and anti-tumor chemotherapy by administration of erythropoeitin - P. BOWERS; L. ITRI (2004)
本发明提供使用促红细胞生成素改善包含干扰素的抗病毒和抗肿瘤化疗治疗方案的耐受性的方法。本发明还描述了如下治疗慢性HCV的改良方法：调整三氮唑核苷的剂量以定制药物的有效剂量，同时用EPO支持患者的血红蛋白水平。本发明还提供抗病毒给药治疗方案，尤其是用于治疗慢性HCV的给药治疗方案，所述给药治疗方案包括给予包含干扰素的抗病毒药物、EPO以及降低患者体内活性肿瘤坏死因子量的化合物。 The present invention provides methods using erythropoietin to improve the tolerance of anti-viral and anti-tumor chemotherapeutic regimens containing interferon. The invention also described improved methods to treat chronic HCV by adjusting the dose of ribavirin to tailor the active dose of the drug while supporting the hemoglobin levels in the patient with EPO. The present invention also provides anti-viral dosing regimens, particularly for chronic HCV comprising administration of an interferon containing anti-viral medicament, EPO, and a compound that reduces the amount of active tumor necrosis factor in the subject.